Early phase changes by concurrent endurance and strength training - Balabinis, C. P.; Psarakis, C. H.; Moukas, M. (The Journal of Strength and Conditioning Research, 2003)
To compare regimens of concurrent strength and endurance training, 26 male basketball players were matched for stature, body composition, and physical activity level. Subjects completed different training programs for 7 weeks, 4 days per week. Groups were as follows: (a) the strength group (S; n = 7) did strength training; (b) the endurance group (E; n = 7) did endurance training; (c) the strength and endurance group (S + E; n = 7) combined strength and endurance training; and (d) the control group (C; n = 5) had no training. The S + E group showed greater gains in O2max than the E group did (12.9% vs. 6.8%), whereas the S group showed a decline (8.8%). Gains were noted in strength and vertical jump performance for the S + E and S groups. The S + E group had better posttraining anaerobic power than the S group did (6.2% vs. 2.9%). No strength, power, or anaerobic power gains were present for the E and C groups. We conclude that concurrent endurance and strength training is more effective in terms of improving athletic performance than are endurance and strength training apart.